(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This article analyzes the organizational and methodological aspects of effectively organizing and conducting football competitions among students. The study examines factors such as planning sports events in higher education institutions, developing competition regulations, refereeing systems, and assessing participants’ preparedness. The significance of football competitions in increasing students’ physical activity, enhancing interest in sports, and promoting a healthy lifestyle is substantiated. The article also provides effective methods for organizing competitions and practical recommendations for organizers and coaches. Based on the findings, proposals and conclusions have been developed to help enhance students’ sports potential.